2001
DOI: 10.1093/ps/80.10.1412
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation of Eimeria maxima oocysts in litter with different moisture contents

Abstract: The aim of this study was to determine if the sporulation of Eimeria maxima oocysts was affected by the moisture content of the litter. Fresh feces were collected from chickens experimentally infected with E. maxima. The feces were mixed with dried wood shavings and different amounts of water to obtain final moisture contents of 16, 42, and 62% and a final oocyst concentration of 5,000 per g of mixture. The samples were kept at 23 C and 75% relative humidity and were thoroughly aerated every 12 h. Oocysts kept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
4

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 7 publications
2
26
0
4
Order By: Relevance
“…apparent adverse effects on the performance of the Tso31 nested PCR. Potassium dichromate is widely used for preservation and viability studies of different parasites present in fecal specimens (17,27,28,29); it has also been reported to be used for DNA recovery from cryptosporidium parasites (16).…”
Section: Discussionmentioning
confidence: 99%
“…apparent adverse effects on the performance of the Tso31 nested PCR. Potassium dichromate is widely used for preservation and viability studies of different parasites present in fecal specimens (17,27,28,29); it has also been reported to be used for DNA recovery from cryptosporidium parasites (16).…”
Section: Discussionmentioning
confidence: 99%
“…Research data have shown that in the field sporulation in wet litter is suboptimal possibly due to the occurrence of ammonia and bacteria (Williams 1995); in fact, dry litter showed better sporulation rates (Graat et al 1994;Waldenstedt et al 2001). However, increasing the litter humidity as a control measure to reduce sporulation does not seem feasible as it might cause footpad lesions and skin burns in the birds.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Concerning aqueous potassium dichromate, a concentration of 2-2.5 % at 22°C provides the optimum laboratory conditions for sporulation of Cyclospora, Isospora and Eimeria oocysts. (Waldenstedt et al 2001;Göz and Aydin 2005;Sathyanarayanan and Ortega 2006;Yazar et al 2006). Placing Cryptosporidium baileyi oocysts in 2.5 % potassium dichromate maintained their viability for 18 months, although death of some oocysts may occur within the initial 24 h but with no further reduction in viability (Surl et al 2003).…”
Section: Discussionmentioning
confidence: 99%